2011
DOI: 10.1016/j.physletb.2010.11.052
|View full text |Cite
|
Sign up to set email alerts
|

Determining reaction cross sections via characteristic X-ray detection: α-induced reactions on 169Tm for the astrophysical γ-process

Abstract: The cross sections of the 169 Tm(α,γ) 173 Lu and 169 Tm(α,n) 172 Lu reactions have been measured first time using a new method, by detecting the characteristic X-ray radiation following the electron capture-decay of 172,173 Lu. Despite the relatively long half-life of the reaction products (T 1/2 = 500 and 6.7 days, respectively) it was possible to measure the cross section of the 169 Tm(α,γ) 173 Lu reaction close to the Gamow window (T 9 = 3.5 GK), between E c.m. = 13.16 and 17.08 MeV. The 169 Tm(α,n) 172 L… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
82
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 56 publications
(87 citation statements)
references
References 25 publications
5
82
0
Order By: Relevance
“…This approach provides more relevant astrophysical information than the direct study of the γ -induced reactions since often the influence of thermally excited states is smaller in this direction, compared to photon-induced reactions [16,[22][23][24]. In recent years several α-capture cross sections have been measured using the well known activation technique [25][26][27][28][29][30][31][32][33], and the results were compared with the H-F predictions. In general, it was found that the H-F cross sections are very sensitive to the choice of the α + nucleus OMP, in particular at energies significantly below the Coulomb barrier, which is the most relevant energy range for the calculation of stellar reaction rates.…”
Section: A the Astrophysical γ Processmentioning
confidence: 99%
“…This approach provides more relevant astrophysical information than the direct study of the γ -induced reactions since often the influence of thermally excited states is smaller in this direction, compared to photon-induced reactions [16,[22][23][24]. In recent years several α-capture cross sections have been measured using the well known activation technique [25][26][27][28][29][30][31][32][33], and the results were compared with the H-F predictions. In general, it was found that the H-F cross sections are very sensitive to the choice of the α + nucleus OMP, in particular at energies significantly below the Coulomb barrier, which is the most relevant energy range for the calculation of stellar reaction rates.…”
Section: A the Astrophysical γ Processmentioning
confidence: 99%
“…In this direction the influence of thermally excited states remains relatively small [7,8]. In recent years a range of (α,γ ) reaction cross sections on 70 Ge, 96 Ru, 106 Cd, 112,117 Sn, 113 In, 144 Sm, 151 Eu, and 169 Tm has been measured using the activation method, and the results have been compared with model predictions [9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a number of α-beam activation measurements have been conducted for targets relevant to pprocess [5][6][7][8][9][10][11][12][13]. Cross sections of the corresponding (α,x) reactions were measured at, or close to, the astrophysically relevant energy.…”
mentioning
confidence: 99%